Linking Isotope Exchange with Fe(II)-Catalyzed Dissolution of Iron(hydr)oxides in the Presence of the Bacterial Siderophore Desferrioxamine-B - Biswakarma, Jagannath (Environ Sci Technol, 2019)
[Image: see text] Dissolution of Fe(III) phases is a key process in making iron available to biota and in the mobilization of associated trace elements. Recently, we have demonstrated that submicromolar concentrations of Fe(II) significantly accelerate rates of ligand-controlled dissolution of Fe(III) (hydr)oxides at circumneutral pH. Here, we extend this work by studying isotope exchange and dissolution with lepidocrocite (Lp) and goethite (Gt) in the presence of 20 or 50 μM desferrioxamine-B (DFOB). Experiments with Lp at pH 7.0 were conducted in carbonate-buffered suspensions to mimic environmental conditions. We applied a simple empirical model to determine dissolution rates and a more complex kinetic model that accounts for the observed isotope exchange and catalytic effect of Fe(II). The fate of added tracer (57)Fe(II) was strongly dependent on the order of addition of (57)Fe(II) and ligand. When DFOB was added first, tracer (57)Fe remained in solution. When (57)Fe(II) was added first, isotope exchange between surface and solution could be observed at pH 6.0 but not at pH 7.0 and 8.5 where (57)Fe(II) was almost completely adsorbed. During dissolution of Lp with DFOB, ratios of released (56)Fe and (57)Fe were largely independent of DFOB concentrations. In the absence of DFOB, addition of phenanthroline 30 min after tracer (57)Fe desorbed predominantly (56)Fe(II), indicating that electron transfer from adsorbed (57)Fe to (56)Fe of the Lp surface occurs on a time scale of minutes to hours. In contrast, comparable experiments with Gt desorbed predominantly (57)Fe(II), suggesting a longer time scale for electron transfer on the Gt surface. Our results show that addition of 1–5 μM Fe(II) leads to dynamic charge transfer between dissolved and adsorbed species and to isotope exchange at the surface, with the dissolution of Lp by ligands accelerated by up to 60-fold.